2010
DOI: 10.1097/qad.0b013e32833b5256
|View full text |Cite
|
Sign up to set email alerts
|

A TRIM5α exon 2 polymorphism is associated with protection from HIV-1 infection in the Pumwani sex worker cohort

Abstract: Objective The innate immune component TRIM5α has the ability to restrict retrovirus infection in a species-specific manner. TRIM5α of some primate species restricts infection by HIV-1, while huTRIM5α lacks this specificity. Previous studies have suggested that certain polymorphisms in huTRIM5 may enhance or impair the proteins affinity for HIV-1. This study investigates the role of TRIM5 polymorphisms in resistance/susceptibility to HIV-1 within the Pumwani sex worker cohort in Nairobi, Kenya. A group of women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
38
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 24 publications
4
38
0
1
Order By: Relevance
“…15 Previous studies, including ours, showed the reduced antiviral activity of the H43Y substitution, but the associations with HIV-1 infection and disease progression were inconsistent among studies.…”
mentioning
confidence: 89%
“…15 Previous studies, including ours, showed the reduced antiviral activity of the H43Y substitution, but the associations with HIV-1 infection and disease progression were inconsistent among studies.…”
mentioning
confidence: 89%
“…In addition, overall hTRIM5␣ activity can be influenced by its induction by IFN-␣ (44,86,87) and the relative expression of hTRIM5␣ and the inhibitory hTRIM5 splicing variants (gamma, delta, iota) (88). Furthermore, several hTRIM5␣ allelic variants have been identified with impaired activity, including those carrying the H43Y and G249D polymorphisms, although both the effect of these polymorphisms on TRIM5␣ activity and the impact of expression of these variants on disease progression remain controversial (44,83,(89)(90)(91)(92)(93)(94)(95)(96)(97). Interestingly, strain-specific differences in CA can also influence viral sensitivity to different TRIM5␣ allelic variants (44,83).…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Nonetheless, cohort studies indicate that selected huTRIM5α alleles are associated with altered HIV-1 disease progression, [18][19][20][21] suggesting that huTRIM5α does play a role in ameliorating HIV-1 pathogenesis. Importantly, selected mutations within huTRIM5α that mirror rhTRIM5α dramatically augment restriction activity, with only a single substitution (R332P) required within the B30.2/SPRY domain to confer measureable restriction activity in single-round assays, 22 and as few as five substitutions within the B30.2/SPRY domain conferring potent restriction activity approaching that of rhTRIM5α.…”
Section: Introductionmentioning
confidence: 99%